Characterization of the total family risk among families with functional elder adults, in the area of "Patio Bonito", in Bogotá, 2005 Caracterización del riesgo familiar total en las familias con adultos mayores funcionales, sector de Patio Bonito, Bogotá, 20051 - VELÁSQUEZ VELÁSQUEZ CAROL IVONNE; FLORISA VELÁSQUEZ GUTIÉRREZ VILMA FLORISA (Avances en Enfermería, 2007)
This article is generated based on the results of a master's degree research that unveiled the characteristics of the total family risk among families with functional elder adults who are beneficiaries of the Care Program for the wellbeing of the elderly who are poor, of the Local Health Center, the "Centro Operativo Local de Kennedy", i.e. residents in the area of "Patio Bonito". Data was obtained using the RFT 7-70 instrument, designed by Dr. Pilar Amaya. The research showed in general terms the characteristics of family structures and the tabulation of total family risks having as high some 34,7%, as medium some 34,7% among the group of families; also it enable one to identify the sub categories and risk factor that are most frequent in such family systems, which may be useful as a tool when planning and carrying out health programs for families according to risk. Este artículo presenta parte de los resultados del proyecto de investigación Caracterización de familias beneficiarias del programa Atención para el bienestar del adulto mayor en situación de pobreza del Centro Operativo Local de Kennedy, financiado por la División de Investigación Bogotá, en el cual se describen las características y el riesgo familiar total de 72 familias con adultos mayores funcionales, mediante el uso del instrumento RFT 7-70, elaborado por Pilar Amaya. La investigación muestra las características de la estructura familiar, la calificación similar del riesgo familiar total alto y medio (34.7%) y las subcategorías más frecuentes en dichas familias, resultados que pueden ser útiles en el momento de planear y desarrollar programas de salud familiar con enfoque de riesgo.